STUDENT STEAM CHAMPION: PENERAPAN INTEGRASI SAINS, TEKNOLOGI, TEKNIK, SENI, DAN MATEMATIKA DALAM PEMBELAJARAN MATEMATIKA DI MI MAARIF BLENDANGAN - Azizatul Alif Syafriza; Putri Zudhah Ferryka; Yuninda Dwindiyantik; Desinta Anjar Wati; Muhammad Rif’an Baroz (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2026)
The purpose of the "Student STEAM Champion" community service program is to provide meaningful learning experiences for MI Maarif Blendangan students. Meaningful mathematics learning is carried out by directly involving students in the learning process. Mathematics learning is carried out in a fun and interactive manner, increasing student motivation. Students understand mathematical concepts better. Students have the opportunity to develop critical thinking skills and collaboration among students